Differences in government accounting conservatism across jurisdictions, their determinants, and consequences: the case of Canada and the United States - Cziffra, Johnathon; Fortin, Steve; Singer, Zvi (Review of Accounting Studies, 2023)
We use the year-end adjustments to the provisions for student loan losses of state and provincial governments in the United States and Canada to study government accounting conservatism and how it varies between these adjacent and highly integrated countries. Building on Canada’s more conservative cultural attributes, we hypothesize and find that Canadian provincial governments report more conservative provisions for student loan losses than U.S. state governments. Moreover, the year-end adjustments to the provisions in Canada are excessively conservative; they are larger than the audit materiality threshold. We further find that the political ideology of the government, government reporting incentives, government debt, and political competition are important determinants of government accounting conservatism. Finally, we find a negative association between the year-end adjustment to the provision and future student lending. This result suggests that government accounting conservatism leads to credit rationing and significant societal consequences for students. Overall, our study highlights important aspects of the determinants and consequences of government accounting conservatism. To the best of our knowledge, this study is the first to examine government unconditional accounting conservatism.